Chronic Pain Opioid-Maintained Patients Receive Less Analgesic Opioid Prescriptions - Delorme, Jessica; Chenaf, Chouki; Bertin, Celian; Riquelme, Marie; Eschalier, Alain; Ardid, Denis; Authier, Nicolas (Frontiers in Psychiatry, 2018)
Treating pain and opioid use disorder represents a clinical challenge. While most studies that have assessed opioid analgesic use in opioid substitution treatment (OST) patients primarily address opioid analgesic misuse (Brands et al., 2004; Rosenblum et al., 2007), only few studies focused on OST patients assessed the prescription of analgesic opioids for chronic pain. We sought to compare the prevalence of analgesic opioid prescription (AOP) in two groups of chronic non-cancer pain (CNCP) patients: OST patients versus the general population. This was a population-based cross-sectional study based on the French national healthcare claims database SNIIRAM (Système National d’Informations Inter-Régimes de l’Assurance Maladie) covering over 66 million people (98,8% of the French population). Overall, 67,173 participants ≥15 years old undergoing continuous OST in 2015 (“OST patients” group) were included and age- and gender-matched by means of a 1:1 ratio with 67,173 patients without OST (“control” group). In each group, patients with cancer conditions were excluded and those having received opioid and non-opioid analgesics for at least 3 months were identified (CNCP patients). Compared to control patients, CNCP OST patients received less AOP (47.8% vs. 68.0%, p <0.0001) and more often non-opioid prescription (52.2% vs. 32.0%, p <0.0001). In multivariate analysis, CNCP OST patients were 2.7 times less likely to be prescribed analgesic opioids (adjusted odds ratio [OR]=2.7 [2.42-3.01], p <0.0001) than control patients. AOP correlated in CNCP OST patients with: age ≤40 years old, female gender, low-income status, methadone-maintained treatment, mental health disorder, hepatitis C virus (HCV) infection, and alcohol abuse disorder. Opioid analgesics were less often prescribed in CNCP OST patients. AOP prevalence was 2.7-fold lower than in the general population. Chronic pain management in OST patients needs to be reinforced through additional physician training and a multidisciplinary approach.